Towards the Multidimensional Ushul Al-Fiqh: A Study of the Integration of Science in the Fatwa of Majelis Ulama Indonesia - Thahir, A. Halil (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This research examines multidimensional ushul al-fiqh in analyzing the fatwas of the Majelis Ulama Indonesia (MUI). The main problem to be explained in this article is the importance of social sciences for multidimensional ushul al-fiqh as contained in the fatwa of the Indonesian Ulema Council. This research uses normative juridical methods which are analyzed using the ushul fiqh theory. The data collection method is documentation, namely taking data from journal articles books, and other sources. The method of analysis is the content analysis that the researchers use using the theory of multidimensional ushul al-fiqh, while the object is the fatwa-fatwa of the Majelis Ulama Indonesia (MUI). This research has two results. First, the social sciences complement the evidence of fundamentalist rulings in realizing the natural environmental influences, as a basic determinant and a major guide to people's lives, and the jurisprudence of social movements, of all kinds, considering the ties that bind people, and exploring the depths of the soul Humanity, considering the human being the pivot and the basis of this existence, so that the rulings derived from it are in agreement and conformity according to social issues. Secondly, the fatwas of the Council of Indonesian Scholars in the social field include those based on social sciences in addition to fundamental principles such as the Qur’anic texts and the Sunnah of the Prophet. In the context of ushul fiqh theory, it increasingly proves that fatwas and social sciences are quite dynamically integrated. This is evident in the fatwa of massage parlors and the sending of female workers abroad. Among them were those who were more inclined to fundamentalist rules than to pay attention to the social sciences, such as the fatwa on interfaith marriage and the celebration of Christian birth.